Lower urinary tract symptoms in children and adolescents with Williams-Beuren syndrome. Issue 2 (April 2017) - Sammour, Z.M.; de Bessa Jr, J.; Hisano, M.; Bruschini, H.; Kim, C.A.; Srougi, M.; Gomes, C.M.
Summary: Introduction: Williams-Beuren syndrome (WBS) is a genetic condition caused by a microscopic deletion in the chromosome band 7q11.23. Individuals with WBS may present with congenital cardiovascular defects, neurodevelopmental disturbances and structural abnormalities of the urinary tract. Lower urinary tract symptoms (LUTS) seem to be frequent in this population, but studies on this topic are scarce and based on small case series. Objective: To systematically evaluate the prevalence of lower urinary tract symptoms (LUTS) and the acquisition of bladder control in a large population with WBS. Study design: A cross-sectional study evaluating 87 consecutive patients with WBS; there were 41 girls and 46 boys. Genetic studies confirmed WBS in all patients. Subjects were clinically evaluated with: a history of LUTS obtained from the parents and child, a structured questionnaire of LUTS, a 3-day urinary frequency-volume chart, a quality of life question regarding LUTS, and physical examination. A history regarding the acquisition of bladder control was directly evaluated from the parents. Results: Mean age of patients was 9.0 ± 4.2 years, ranging from 3 to 19 years. Based on the symptoms questionnaire and the frequency-volume chart, 70 patients (80.5%) were symptomatic. The most common symptom was urgency, affecting 61 (70.1%) patients, followed by increased urinary frequency in 60 (68.9%) patients, and urge-incontinence in 53 (60.9%), as shown in Summary Fig. More than half of the children reported nocturnal enuresis, including 61% of the girls and 52% of the boys. Twenty-three patients (25.6%) had a history of urinary tract infections. The mean age for acquisition of dryness during the day was 4.4 ± 1.9 years. Parents of 61 patients (70.1%) acknowledged that LUTS had a significant impact on the quality of life of their children. Discussion: A high prevalence of LUTS was confirmed with a significant negative impact on quality of life in a large population of children and adolescents with WBS. It was shown for the first time that the achievement of daytime bladder control is delayed in children with WBS. Although LUTS are not recognized as one of the leading features of the syndrome, it is believed that it should be considered as a significant characteristic of the clinical diagnosis of WBS. Conclusions: LUTS are highly prevalent in children and adolescents with WBS and have a significant negative impact on patient's quality of life. Summary Fig Frequency of urinary symptoms in patients with Williams-Beuren syndrome.